Perancangan Desa Wisata Kadisoro Nyawiji Dadi Siji (KAJII), Kapanewon Pandak, Kabupaten Bantul - Setiadi, Amos; Binarti, Floriberta; Armando, Nicolas; Pitaloka, Anastasya (Jurnal Atma Inovasia, 2023)
This Community Service activity aims to encourage the region as a partnership model for Higher Education to impact community welfare through community partnership-based Master Plan design assistance and services. The method used to achieve this goal is problem-solving through identifying village potentials carried out by universities to provide design services. The steps include coordinating with the OPD through the Bantul Regency Tourism Office, surveying locations, and formulating a design for identifying potentials that are expected to become icons and tourist destinations for the Gilangharjo village area in Kapanewon Pandak. It is hoped that the activity plans prepared in the Community Service for lecturers and Student Practical Work courses are aligned with the MBKM for students and help accelerate the achievement of the Bantul Regency RPJM, especially for the Gilangharjo Kapanewon Pandak Village area. The outputs of the Community Service activities in Gilangharjo Village are identification or pre-designed albums and scientific articles in the Community Service journal. The focus of this activity is to solve the problem of identifying village potential so that it has a tourist attraction and improves the appearance of the environment and accommodates the socio-cultural values of the community. The activities that will be carried out are outer space design, which needs to be organized. This activity will also produce a picture album/identification of village potential that involves students as a form of MBKM partnering with the Tourism Office and Gilangharjo Village